Intention to use Online Food Delivery (OFD) service among student in University Technology MARA Dungun Campus / Nurul Syazwani Sahidi and Nuraina Syazana Mohd Shukri @ Alias - Sahidi, Nurul Syazwani; Mohd Shukri @ Alias, Nuraina Syazana (2021)
This research proposal will be carry out with the topic of intention to use online food delivery service among student in University Technology MARA Dungun Campus. Recently, we have been interest to understand student behavior related to the use of online food delivery service when purchasing food from via online platform. However, the various motives behind the usage of online food delivery service among university student have not been addressed. Hence, this study worked to fill this gap by developing a methodology, sample and questionnaire that comes up with a reliable initiatives that measures purposes and reasons behind the customer usage of online food delivery service. Additionally, the association between purposes as well as reasons and intentions to use online food delivery service were investigated. The study found five main factors behind the use of food delivery service, namely, price saving, time saving, perceived ease of use, convenience motivation and flexible payment. The study concludes with various implications and recommendations for future research on customer’s intention to use online food delivery service.